Britain : for learners of English [: student's book]. - O'Driscoll, James, ....- (Oxford : University Press, 2009)
Understand the country and its people with this culture guide that gives a real insight into what it means to live in Britain today. Completely updated, Britain 2nd edition provides the historical and cultural background to British society and institutions such as the NHS and the BBC as well as an insight into the private daily life of the British people. Students are encouraged to think about the cultural issues raised and to make comparisons with their own culture.
Keywords: Engels; Engelse woordenschat; Groot-Brittannië.; Vreemde-talenonderwijs.